Early life maltreatment and resting-state heart rate variability: a systematic review and meta-analysis - Sigrist, Christine; Mürner-Lavanchy, Ines M.; Peschel, Stephanie; Schmidt, Stefanie; Kaess, Michael; Koenig, Julian (Neuroscience & biobehavioral reviews, 2021)
Recent focus on the consequences of early life adversity (ELA) in neurobiological research led to a variety of findings suggesting alterations in several physiological systems, such as the cardiovascular system. In this systematic review and meta-analysis, we focused on the relationship between early life maltreatment (ELM), one form of ELA, and resting vagal activity indexed by resting-state heart rate variability (HRV). A systematic search of the literature yielded 1′264 hits, of which 32 studies reporting data for group comparisons or correlations were included. By quantitative synthesis of existing studies using random-effect models, we found no evidence for a relationship between ELM exposure and resting vagal activity in principal. Conducting meta-regression analyses, however, we found the relationship between ELM and resting vagal activity to ignificantly vary as a function of both age and the presence of psychopathology. In light of the current multitude of vastly unclear pathways linking ELM to the onset of disease, we emphasize the need for further research and outline several aspects to consider in future studies.